EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PERMAINAN TRADISIONAL PADA MATERI BANGUN DATAR SISWA KELAS IV SD INPRES BONTOMANAI - Ramadhani, Magfirah; Nasrun; Alim Syahri, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of mathematics learning through traditional games of engklek on the material of plane figures of fourth-grade students of SD Inpres Bontomanai. This pre-experimental study with a one-group pretest-posttest design involved 31 students as a total sample. The effectiveness of learning was reviewed from learning outcomes, student and teacher activities, and student responses. The results showed a significant increase in learning outcomes, marked by an average pre-test score of 43.55 increasing to 85.16 in the post-test with an N-Gain of 0.71 in the high category. Student activity was in the active category with an average percentage of 73.71%, teacher activity was in the good category with an average value of 3.17, and student responses to learning through engklek games were classified as very positive with a percentage of 81.8%. Based on these results, it can be concluded that the application of traditional engklek games is effective in learning mathematics on plane figures for fourth-grade students of SD Inpres Bontomanai.